Increases in understory plant cover and richness persist following restoration treatments in Pinus ponderosa forests - Springer, Judith D.; Stoddard, Michael T.; Rodman, Kyle C.; Huffman, David W.; Fornwalt, Paula J.; Pedersen, Rory J.; Laughlin, Daniel C.; McGlone, Christopher M.; Daniels, Mark L.; Fulé, Peter Z.; Moore, Margaret M.; Kerns, Becky K.; et al. (The Journal of applied ecology, 2024)
A combination of forest thinning followed by prescribed burning is widely applied in the western United States to increase ecosystem resistance and resilience to disturbances. Understory plant community responses may be driven by both management treatments and climatic factors. Thus, responses to treatments during a 20‐year megadrought have implications for the role of management in fostering adaptive capacity to climate change. We used a network of five sites (600 plots) spanning an environmental gradient in ponderosa pine ( Pinus ponderosa ) forests of the American Southwest, an ecosystem that is broadly distributed and actively managed throughout the western United States. We used repeated long‐term monitoring data to quantify plant community responses to treatment 1–5‐, 6–10‐ and >10‐year post‐implementation. Specifically, we focussed on the effects of treatment and abiotic conditions on native and non‐native plant cover and species richness and the proportion of native species with northern (cool‐mesic) biogeographic affinities. Overall, thinning and prescribed burning nearly doubled native cover and increased native species richness by about 50% relative to untreated controls. These effects persisted for over a decade after treatment, even under the influence of significant and persistent drought. Cover and richness were also greater on intermediate to wet sites. Finally, native species with northern biogeographic affinities were reduced for up to 5 years after treatment relative to those with southern (warm‐xeric) affinities, and in dry years, indicating that both management and interannual climate variability may foster shifts to plant communities that are more resilient to a warming climate. Synthesis and applications . In ponderosa pine forests of the American Southwest, tree thinning followed by prescribed burning will generally promote restoration goals of increasing resilience to climate change by enhancing the diversity and abundance of native understory plant species, even during a persistent 20‐year megadrought.